Development of Web Quest Lesson Enhancing Thai Reading Skills for Students with Down Syndrome at Lower Elementary - Kaewchote, Nantawan; Chongchaikit, Maturos (Journal of the American Academy of Special Education Professionals, 2012)
The purpose of this research was to enhancing the Thai language oral reading skills of lower elementary students with Down syndrome using WebQuest lesson. The sample groups were the 5 lower elementary students, purposively selected from Watnonsaparam public school under the Office of Saraburi Educational Service Area, Thailand. The research instruments were the Thai language reading tests for students with Down syndrome, the WebQuest lesson with 12 units based on Thai language oral reading problems of students with Down syndrome, the two observation forms for Thai language oral reading tests. The findings revealed that Thai language oral reading problems of the students with Down syndrome varied greatly on the pronunciation of consonants, vowels, tone marks, different kinds of words and short sentences. Nevertheless, at first round of WebQuest usage, the four of five students with Down syndrome were able to correctly pronounce the Thai alphabets and show the understanding of basic reading skill. Most of them had problems with Thai vowels in terms of both the pronunciation and the meaning decoding; they took much more time than usual to read. The students’ usage of WebQuest had led to the improvement of Thai oral reading lesson to suit more the needs of students with Down syndrome. The new menus for skill practices, resource searching and communication among students, parents and teachers were added, as well as some graphics and symbols. More sounds were put to accompany all words and sentences of WebQuest lesson.